FLOUTING MAXIM ANALYSIS ON BBC RADIO 1 YOUTUBE CHANNEL “KIDS ASK RYAN REYNOLDS” - Adenan Damiri; Aida Fiskaryanti; Billi Andara Nainggolan; Nidia Amalia (Universitas Pamulang, 2023)
This study discusses the analysis of the flouting maxim using a YouTube video on the BBC Radio 1 YouTube channel